1970
DOI: 10.1017/s0022172400042339
|View full text |Cite
|
Sign up to set email alerts
|

Experimental encephalitis following peripheral inoculation of West Nile virus in mice of different ages

Abstract: SUMMARYExperimental arbovirus infections of mice provide a convenient model to study factors which determine the occurrence or severity of encephalitis following extraneural infection with certain neurotropic viruses. Varying doses of West Nile or Powassan viruses were inoculated by intraperitoneal or intramuscular routes into mice of varing ages; individual variables were manipulated to influence the outcome of infection. Three patterns of pathogenesis were delineated: (1) Fatal encephalitis, preceded by earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 22 publications
6
48
1
Order By: Relevance
“…Many strains of WNV are neuroinvasive and can induce fatal encephalitis in mice and humans (18,52,58). In the present study, we investigated the mouse-virulent Sarafend strain of WNV as a model of WNV-induced encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Many strains of WNV are neuroinvasive and can induce fatal encephalitis in mice and humans (18,52,58). In the present study, we investigated the mouse-virulent Sarafend strain of WNV as a model of WNV-induced encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…2) (Albrecht, 1968;Nathanson, 1980). Three patterns of pathogenesis have been defined (Weiner et al, 1970;Nathanson, 1980): (1) fatal encephalitis usually preceded by early viremia and extensive extraneural replication; (2) subclinical encephalitis, usually preceded by low viremia, late establishment of brain infection, and clearance with minimal destructive pathology; and (3) inapparent infection, with trace viremia, limited extraneural replication, and no neuroinvasion. The role of immune responses in limiting viral dissemination has been repeatedly demonstrated in experiments employing immunosuppressive agents, which can convert subclinical to lethal encephalitis.…”
Section: A Host Factors That Influence Pathogenesismentioning
confidence: 99%
“…Studies of experimental flavivirus encephalitis in mice have shown a relationship among level of viremia, development of brain infection (Weiner et al, 1970), and widespread or multisite simultaneous appearance of viral antigen in nervous tissue (Albrecht, 1960), supporting the concept of hematogenous spread to the CNS (Johnson, 1982). The process by which flavivirus particles cross the blood-brain barrier remains uncertain.…”
Section: Neuroinvasionmentioning
confidence: 99%
“…Other workers have found that high doses of West Nile virus produced a readily apparent encephalitis with patchy neuronal necrosis, particularly in the cerebral cortex and hippocampus. whereas in a subclinical infection the encephalitis was mild [ 19). A single dose of cyclophosphamide 24 hours after intraperitoneal infection of 10" LD,,, of West Nile virus converted an inapparent mouse brain infection into a lethal infection [4].…”
Section: Discussionmentioning
confidence: 98%